2023
DOI: 10.3390/polym15020386
|View full text |Cite
|
Sign up to set email alerts
|

PEEK for Oral Applications: Recent Advances in Mechanical and Adhesive Properties

Abstract: Polyetheretherketone (PEEK) is a thermoplastic material widely used in engineering applications due to its good biomechanical properties and high temperature stability. Compared to traditional metal and ceramic dental materials, PEEK dental implants exhibit less stress shielding, thus better matching the mechanical properties of bone. As a promising medical material, PEEK can be used as implant abutments, removable and fixed prostheses, and maxillofacial prostheses. It can be blended with materials such as fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 156 publications
0
26
0
Order By: Relevance
“…132 Specifically, PEEK materials possess mechanical properties closely resembling human bone, including a density of 1.3 g cm −3 , Martens hardness of 190 N mm −2 , tensile strength of 100 MPa, elastic modulus of 6 GPa, and bending strength of 170 MPa. 133 However, CFR PEEK is also proposed for hip implant application which is a composite material that strengthens PEEK by adding carbon fibers. This reinforcement significantly enhances the mechanical properties of PEEK, making it stronger, more wear-resistant, and better suited for applications where higher strength and durability are required, such as orthopaedic implants like hip implants.…”
Section: Hip Implant With Various Stem Structuresmentioning
confidence: 99%
“…132 Specifically, PEEK materials possess mechanical properties closely resembling human bone, including a density of 1.3 g cm −3 , Martens hardness of 190 N mm −2 , tensile strength of 100 MPa, elastic modulus of 6 GPa, and bending strength of 170 MPa. 133 However, CFR PEEK is also proposed for hip implant application which is a composite material that strengthens PEEK by adding carbon fibers. This reinforcement significantly enhances the mechanical properties of PEEK, making it stronger, more wear-resistant, and better suited for applications where higher strength and durability are required, such as orthopaedic implants like hip implants.…”
Section: Hip Implant With Various Stem Structuresmentioning
confidence: 99%
“…In addition to the use of chemical, physical, and mechanical approaches to increase the bond strength between PEEK and an adhesive, the adhesive system itself is partly responsible for determining the resulting bond strength. For instance, the combination of an adhesive primer and resin cement has been demonstrated as a reliable adhesive system for bonding PEEK [6,27], wherein methyl methacrylate (MMA)-containing adhesive primers are particularly effective for bonding PEEK to resin cement [27,28]. Previous studies have reported that two MMA-containing primers, namely Visio.link and Signum PEEK Bond, can improve the bond strength of PEEK [6,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The use of polyether ether ketone (PEEK) can solve this problem since the elastic modulus of this polymer is close to that of natural bone [6]. In addition, compared to titanium, PEEK has advantages in terms of manufacturing and processing, which in this case is mainly done by 3D printing [7,8]. However, the main disadvantage of PEEK is its bioinertness, which results in low bioactivity and prevents its integration into bone tissue [6,9].…”
Section: Introductionmentioning
confidence: 99%